Unexpected inflation and public pensions: The case of Hungary - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2023)
Public pensions are indexed to prices or wages or to their combinations; therefore, the impact of inflation on the real value of benefits can often be neglected, especially under indexation to prices. At high and accelerating/decelerating inflation like currently prevailing in Hungary, however, this is not the case. (i) With fast inflation of basic necessities, proportional indexation of benefits in progress devalues the lowest benefits, paying for above-the-average consumption share of these goods. (ii) Annual, lumpy raises in these benefits imply too high intra-year drop in the real value of benefits. (iii) With accelerating inflation, the declining real value of delayed initial benefits may incite immediate retirement. (iv) With unindexed parameter values (like progressivity bending points), the initial benefits' structure unintentionally changes.
Keywords: E31; H55; 330; inflation; public pensions; indexation; progressivity of initial benefits; delayed retirement